2012
DOI: 10.5433/1679-0359.2012v33supl1p2705
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades físicas das sementes de pinhão-manso ao longo da secagem em diferentes temperaturas

Abstract: ResumoDiante do destaque do pinhão-manso (Jatropha curcas L.) no cenário nacional e internacional e da importância do conhecimento das suas propriedades físicas para a contribuição no desenvolvimento de maquinários que auxiliem no processamento pós-colheita das sementes dessa cultura, objetivou-se com o presente trabalho determinar a porosidade intergranular e as massas específicas aparente e unitária das sementes de pinhão-manso submetidas à secagem em diferentes temperaturas do ar. O experimento foi desenvol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
1
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
3
6
1
6
Order By: Relevance
“…Thus, the true density of safflower grains showed a trend similar to that of the bulk density. A similar trend to that of the present study for the true density has also been found for other species, such as for seeds of cucurbits (Milani et al, 2007), jatropha (Siqueira et al, 2012a), grains of pistachio and peanut (Araujo et al, 2014).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Thus, the true density of safflower grains showed a trend similar to that of the bulk density. A similar trend to that of the present study for the true density has also been found for other species, such as for seeds of cucurbits (Milani et al, 2007), jatropha (Siqueira et al, 2012a), grains of pistachio and peanut (Araujo et al, 2014).…”
Section: Resultssupporting
confidence: 75%
“…However, Seifi et al (2010), working with safflower grains, variety Goldasht, found a similar trend to that found in the present study, as already observed for other crops, such as jatropha seeds (Siqueira et al, 2012a), melon seeds (Bande et al, 2012) and pistachio grains .…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…According to Figure 1, the hygroscopic equilibrium curves obtained through desorption and adsorption for bean grains showed a sigmoid shape, typical of many agricultural products: Chaves et al (2015); Hassini et al (2015), Oliveira et al (2010;2014a;b); Siqueira et al (2012); Smaniotto et al (2012); Sousa et al (2013) and Costa et al (2013). It is also observed that the increase of temperature promotes reduction in the equilibrium moisture content of the grains, following the same tendency of the other agricultural products.…”
Section: Resultsmentioning
confidence: 85%
“…BOTELHO et al (2015), avaliando a influência da temperatura na massa específica aparente de grãos de soja, observaram resultados contrários aos encontrados neste estudo, em que a massa específica dos grãos de soja reduziu em função do incremento de temperatura, indicando prejuízo à qualidade desse produto. SIQUEIRA et al (2012b), em um estudo das propriedades físicas das sementes de pinhão-manso ao longo da secagem em diferentes temperaturas, e SMANIOTTO et al (2017) observaram que a redução do teor de água favorece a redução da massa específica aparente, corroborando os resultados obtidos no presente trabalho.…”
Section: Resultsunclassified